Chronic kidney disease detection using ensemble classi ers and feature set reduction - Shawan, Naveed Rahman; Mehrab, Syed Samiul Alam; Ahmed, Fardeen; Hasmi, Mohammad Sharatul (BRAC University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2019.